Răspuns :
Răspuns:
Explicație pas cu pas:
7x + 7y = 7*(x + y)
____________
ma^2 + na^2 - xa^2 = a^2*(m + n - x)
_____________
-81m^3 - 9m^4 = -9m^3*(9 + m)
____________
-5x + 5y = 5*(-x + y)
____________
px^2 + p + pa = p*(x^2 + 1 + a)
___________
x√3 + y√3 = √3*(x + y)
____________
ax + ay = a*(x + y)
___________
a(x + y) + b(x + y) = (x + y)(a + b)
____________
√2a - √2b = √2(a - b)
a) 7(x+y)
b) 5(-x+y)
c) a(x+y)
d) a la puterea a 2-a(m+n-x)
e) p(x la a 2-a+1+a)
f) (x+y)(a+b)
g) -m la a 3-a•9(9+m)
h) radical din 3(x+y)
i) radical din 2(a-b)
b) 5(-x+y)
c) a(x+y)
d) a la puterea a 2-a(m+n-x)
e) p(x la a 2-a+1+a)
f) (x+y)(a+b)
g) -m la a 3-a•9(9+m)
h) radical din 3(x+y)
i) radical din 2(a-b)